Additive manufacturing and characterization of hollow core metal and topas waveguides for Terahertz sensor systems - Shrotri, Abhijeet Narendra; Mukherjee, Amlan kusum; Lohöfener, Sven; Springer, André; Stübbe, Oliver; Preu, Sascha (conference digest 48. International Conference on Infrared, Millimeter and Terahertz Waves (IRMMW-THz))
Additive manufacturing provides a lucrative alternative for manufacturing of functional prototypes. This paper emonstrates the manufacturing and characterization of hollow core waveguide prototypes with circular cross section using suitable metal and polymers for Terahertz sensing applications. These additively manufactured waveguide prototypes are characterized from 0.1 to 1.25 THz to evaluate the attenuation and coupling losses.